Regulation of Glutamine Transport in Escherichia coli. - Willis, R C (1975)
The formation of the high-affinity (Km equal to 0.2 muM) L-glutamine transport system of Escherichia coli strain 7 (Lin) appears to be subject to the same major control as the glutamine synthetase (EC 6.3.1.2) of this gram-negative organism. Culture of cells under nitrogen-limited conditions provides maximum derepression of both the glutamine synthetase and the glutamine transport system. Nutritional conditions providing a rich supply of ammonium salts or available sources of nitrogen, i.e., conditions which repress the formation of glutamine synthetase, provide three- and 20-fold repression, respectively, of the glutamine transport system. Culture of cells with glutamine supplements of 2 mM does not increase the repression of high-affinity glutamine transport system beyond the level observed in the absence of glutamine. A second kinetically distinct low-affinity component of glutamine. A second kinetically distinct low-affinity component of glutamine uptake is observed in cells cultured with a glutamine-depleted nutrient broth. This second component is associated with the appearance of glutaminase A (EC 3.5.1.2) and asparaginase I (EC 3.5.1.1), a periplasmic enzyme. Parallel changes were observed in the levels of the high-affinity glutamine transport system and the glutamine synthetase when cells were cultured with the carbon sources: glucose, glycerol, or succinate.